PERSISTENCE OF ANTI-HBs ANTIBODY AND IMMUNOLOGICAL MEMORY IN CHILDREN VACCINATED WITH HEPATITIS B VACCINE AT BIRTH - Jafarzadeh, Abdollah; Montazerifar, Sayed Jalal (Journal of Ayub Medical College Abbottabad, 2006)
Aims: Vaccination with the hepatitis B surface antigen (HBsAg) induces protective levels of antibody (anti-HBs = 10 IU/L) in majority of vaccinees. It has been shown that the levels of anti-HBs antibody do wane after vaccination. The aim of this study was to evaluate the persistence of anti-HBs antibodies in healthy Iranian children at 10 years after primary vaccination and the response to a booster dose using recombinant hepatitis B vaccine. Materials and Methods: Blood samples were collected from 146 healthy 10-11 years old children who received primary course of Hepatitis B vaccine at 0, 1.5 and 9 months of age. The sera were tested for anti-HBs, antibody to Hepatitis B core antigen (anti-HBc) and HBsAg by ELISA technique. A single booster dose of recombinant hepatitis B vaccine was administered intramuscularly to a total of 94 children, whose anti-HBs antibody was less than 50 IU/L (70 children with anti-HBs <10 IU/L and 24 subjects with anti-HBs 10-50 IU/L). The sera of children were re-tested for anti-HBs antibody levels at 4 weeks after booster vaccination. Results: At 10 years after primary vaccination 70/146 (47.9%) of children had protective levels of antibody with geometric mean titer (GMT) of 68.12 IU/ml. All children were negative for HBsAg, although anti-HBc antibody was positive in 11 (7.5%) of children. In the 94 subjects who received the booster dose the seroprotection and the GMT of anti-HBs antibody were 25.5% and 9.58 IU/L at pre-booster time and rose to 95.75% and 575.6 IU/L after the booster vaccination, respectively. Seroprotection rates and mean titer of antibody similarly expressed in males and females. Conclusion: The results of present study showed that at 10 years after primary vaccination with recombinant HB vaccine, 47.9% of the children had protective levels of anti-HBs antibody. Moreover we have demonstrated an anamnestic response to booster vaccination that confirms the persistence of an effective immunological memory in vaccinees. Key words : Children, Hepatitis B vaccine, Anti-HBs antibody, Immunologic memory, Booster vaccination.